2010
DOI: 10.1002/chem.201001240
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Peptide‐Based Hydrogel: A Template for the In Situ Synthesis of Fluorescent Silver Nanoclusters by Using Sunlight

Abstract: N-terminally Fmoc-protected dipeptide, Fmoc-Val-Asp-OH, forms a transparent, stable hydrogel with a minimum gelation concentration of 0.2% w/v. The gelation property of the hydrogel was investigated by using methods such as transmission electron microscopy, field-emission scanning electron microscopy, atomic force microscopy and Fourier transform infrared spectroscopy. The silver-ion-encapsulating hydrogel can efficiently and spontaneously produce fluorescent silver nanoclusters under sunlight at physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(149 citation statements)
references
References 73 publications
5
144
0
Order By: Relevance
“…8a). 83 Here, we believe that some Ag + ions (surface cations 23 not within the channel cavity between the two Gquartets) are photo-reduced in situ. TEM study showed the development of homogeneous small AgNPs having an average diameter of 7 nm within the gel network ( Fig.…”
Section: Functional Gelsmentioning
confidence: 97%
“…8a). 83 Here, we believe that some Ag + ions (surface cations 23 not within the channel cavity between the two Gquartets) are photo-reduced in situ. TEM study showed the development of homogeneous small AgNPs having an average diameter of 7 nm within the gel network ( Fig.…”
Section: Functional Gelsmentioning
confidence: 97%
“…The reducibility of carboxylic groups under a photoreaction has also been put forward by other works [28]. In order to prove the role of carboxylic group, we replaced CM-β-CD by β-CD, which has no carboxylic groups.…”
Section: Role Of Carboxylic Groups On Ag Nanocluster Formationmentioning
confidence: 96%
“…Herein we have attempted to determine the mechanism involved in this reduction. According to the XPS results, silver ions were complexed with the carboxylic group of L-Arginine, and that can significantly decrease the energy barrier for silver-ion reduction [32]. Besides, the guanidine group of L-arginine can interact with ethylene glycol which accelerates the reduction of silver salts with ethylene glycol [33].…”
Section: Mechanism In the Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%